1968
DOI: 10.1037/h0026255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supervisor style and empathy upon counselor learning.

Abstract: Effects of supervisor style (techniques type and counseling type) and supervisor empathy upon counselor learning of empathy in a supervision analogue were examined. 3 groups of 14 Ss heard 2 sets of recorded client statements and responded as counselors. The 2 experimental groups had 20-minute conferences with supervisors (N = 14) between Sets 1 and 2. The control group received no supervision. An analysis of recorded responses indicated that 8a in the techniques and control groups were higher in the learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 12 publications
3
15
0
Order By: Relevance
“…Kelly, 1973;O'Connell, 1974;Payne & Gralinski, 1968;Payne, Weiss, & Knapp, 1972;Payne, Winter, & Ball, 1972;Rappaport et al, 1973;Reddy, 1969aReddy, , 1969bShoemaker, 1973;Stone & Stein, 1978;Toukmanian & Rennie, 1975;Uhlemann, Lea, & Stone, 1976). Conclusions from such studies are not directly generalizable to training actual counselor or clinician trainees.…”
Section: Research Subjects (Trainees)mentioning
confidence: 85%
See 2 more Smart Citations
“…Kelly, 1973;O'Connell, 1974;Payne & Gralinski, 1968;Payne, Weiss, & Knapp, 1972;Payne, Winter, & Ball, 1972;Rappaport et al, 1973;Reddy, 1969aReddy, , 1969bShoemaker, 1973;Stone & Stein, 1978;Toukmanian & Rennie, 1975;Uhlemann, Lea, & Stone, 1976). Conclusions from such studies are not directly generalizable to training actual counselor or clinician trainees.…”
Section: Research Subjects (Trainees)mentioning
confidence: 85%
“…Perhaps the former compensates with precision for what it lacks in interpersonal support. Similarly, several studies have demonstrated that a facilitative supervisory relationship alone is not as effective as supervision in which the supervisor focused on providing specific discriminative feedback, instructions, and modeling as well as on conveying a facilitative interpersonal style (Payne & Gralinski, 1968;Payne, Weiss, & Knapp, 1972;Payne, Winter, & Ball, 1972). A facilitative supervisory approach thus appears to be necessary, but not sufficient for effective training.…”
Section: Supervisory Approachmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the association between femininity and empathy suggests that these students actually feel more empathy. It has previously been shown that empathy shown in trainees does not relate to supervisors' empathy (Payne & Gralinski, 1968). Thus, it is important for the consistency of therapy that trainees choose their counselling course carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these (Payne and Gralinski, 1968;Birk, 1972;Payne, Weiss and Kapp, 1972;Payne, Winter and Bell, 1972;and Carlson, 1974) have found the didactic to be more effective than the experiential in the learning of empathy. On the other hand, Silverman (1972Silverman ( , 1973 found that the experiential approach was more successful in fostering our affective relationships, as perceived by the counselor trainees and their clients.…”
Section: Introductionmentioning
confidence: 99%